1989
DOI: 10.1017/s0950268800030326
|View full text |Cite
|
Sign up to set email alerts
|

The human pathogenic vibrios – A public health update with environmental perspectives

Abstract: Pathogenic Vibrio species are naturally-occurring bacteria in freshwater and saline aquatic environments. Counts of free-living bacteria in water are generally less than required to induce disease. Increases in number of organisms towards an infective dose can occur as water temperatures rise seasonally followed by growth and concentration of bacteria on higher animals, such as chitinous plankton, or accumulation by shellfish and seafood. Pathogenic Vibrio species must elaborate a series of virulence factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0
7

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 233 publications
(280 reference statements)
1
73
0
7
Order By: Relevance
“…The evaluations carried out by West [1] indicated that strains of V. vulnificus are more resistant to lysis by complement than are V. parahaemolyticus and V. cholerae, and that during invasion it can activate both the classic and alternate pathways [2].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The evaluations carried out by West [1] indicated that strains of V. vulnificus are more resistant to lysis by complement than are V. parahaemolyticus and V. cholerae, and that during invasion it can activate both the classic and alternate pathways [2].…”
Section: Resultsmentioning
confidence: 99%
“…Vibrio vulnificus is the most invasive species of the genus Vibrio, with three different clinical syndromes [1]. The first involves progressive infection with a few diarrhoeal symptoms and is characterized by a rapid outset of fulminating septicaemia followed by the appearance of cutaneous lesions with 50 % mortality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, gamma radiation kills the treated oysters, which reduces their shelf life (Dixon and Rodrick 1990). Heat may eliminate V. vulnificus (West 1989), but Lowry et al (1989) reported that 67% of raw oysters and 25% of steamed oysters sampled from 18 downtown New Orleans (USA) restaurants contained V. vulnificus. Cold temperatures have also been suggested; however, Hood et al (1983) reported that levels of V. vulnificus increased slightly in oyster shellstock and shucked meat after 7 d at 4°C.…”
Section: Introductionmentioning
confidence: 99%